Scoping Review: The Role of Micronutrients (Fe, Zn, Iodine, Retinol, Folate) During Pregnancy - Agus Hendra Al Rahmad (Politeknik Kesehatan Kemenkes Mamuju, 2023)
Pregnant women are highly vulnerable to nutritional problems such as Chronic Energy Deficiency (CHD), deficiency of micronutrient intake (iron, zinc, and vitamin A intake), anemia, and Iodine Deficiency Disorder (IDD). Micronutrient deficiencies in pregnant women must be specifically prevented. A healthy and nutritionally balanced diet is essential for maternal and fetal health. The review study aimed to identify the role of micronutrients (Fe, Zn, Iodine, Vitamin A, and Folate) during pregnancy. The literature review used a scoping review technique referring to the Arksey and O'Malley framework. The literature review (2012-2022) used the online databases PubMed, Science Direct, Willey Online Library, ProQuest, and Springer. The search used Medical Subject Headings (MeSH), including the variables